Mapping of the Malaysian regional total electron content (TEC) latitude and longitude profile - Zain, A.F.M; Ho, Yih Hwa; Harun, H (The Institution of Engineers, Malaysia, 2006)
The ionosphere plays a vital role in radio communications whose usable frequencies for signals propagation are mainly affected by its electron content. Determination of the electron content in the ionosphere will aid in reliable and secure radio communications. Phase delays of the received frequencies at L1 (1575.42 MHz) and L2 (1227.6 MHz) of GPS signals has extensively been be used to determine the total electron content of the ionosphere. Using a network of dual frequency GPS receivers in the Malaysian Active GPS System (MASS) installed by the Jabatan Ukur dan Pemetaan Malaysia (JUPEM), a regional map of the Malaysian ionosphere is constructed. This will aid in correcting errors for geomatic and other GPS-based applications. In this paper, techniques to generate the TEC latitude and longitude profile map are discussed. A few sets of the Malaysian regional TEC latitude and longitude profile map have also been produced to demonstrate the dynamic structure of the ionosphere and equator phenomenon such as the famed equatorial anomaly.